Reusability and Reaction Kinetics of Pillared Palm Shell-Based Activated Carbon for Synthetic Dye Adsorption (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2025)
The increasing discharge of synthetic dye effluents from industrial processes poses severe environmental concerns due to their toxicity, persistence, and aesthetic impact on water bodies. This study investigates the reusability potential and reaction kinetics of aluminum/iron-pillared activated carbon derived from palm shell biomass for synthetic dye adsorption. Activated carbon was prepared through carbonization, acid activation, and metal pillaring, followed by multiple adsorption–desorption cycles using a 25 ppm dye solution. Adsorption efficiency was evaluated over five consecutive reuse cycles, while kinetic models including zero-, first-, and second-order reactions were applied to elucidate the adsorption mechanism. Fourier Transform Infrared (FTIR) analysis revealed the presence of functional groups such as hydroxyl, carbonyl, and amine groups, indicating enhanced surface activity after metal pillaring. Results showed that adsorption efficiency peaked at the fourth cycle with a 76.67% color removal before declining due to pore saturation and fouling effects. Kinetic analysis demonstrated that the adsorption process followed a zero-order reaction model (R² = 0.878), suggesting constant adsorption rates independent of dye concentration. These findings highlight the feasibility of reusing pillared palm shell-based activated carbon for wastewater treatment applications and provide insights into its regeneration strategies for sustainable pollutant removal.